Astrocytic Signaling in Persistent Pain - Chu, Yu-Xia; Zhao, Zhi-Qi; Wei, Feng (Current Signal Transduction Therapy, 2012)
Functional sensitization and structural plasticity in the nociceptive pathways and modulatory networks in the peripheral and central nervous system develop following tissue and nerve injury and result in persistent or chronic pain, a major challenge to clinical management. Development of novel analgesic drugs requires a better understanding of the molecular and cellular mechanisms underlying persistent pain. Research during the last three decades has focused on the involvement of neuronal mechanisms in persistent pain. Recently accumulating evidence indicates that reactive glial cells play a critical role in peripheral and central sensitization during the development of persistent pain in variety of animal pain models. The purpose of this review is to highlight important recent advances in astrocytic mechanisms in experimentally persistent pain and the potential to use this information to develop new drugs targeting astrocytic signaling in the treatment of pathological pain.
Keywords: analgesic drugs